Dynamic relationship between infrastructure development and long-term economic growth in Costa Rica, 1983 – 2017 - Santa Cruz Camacho, Camilo (2022)
The development of infrastructure represents a first order condition in the acceleration of the economic growth through different channels that empower off the productivity of the other production factors that compose the goods and services generation processes in an economy. In the next study it is intendent to  verify, with a dynamic econometric model of distributed lags, the impact of the creation of infrastructure over the product level of the Costa Rica economy for the 1983-2017 period; the findings are congruent with the importance that has been given to the infrastructure as a driving force of the economy and it find enlightening to understand the dynamic delayed effects that these have in the growth while there are other research lines that come out as the infrastructure types of very short and short-run, medium and long term and the physic capital, productivity and growth.